2014
DOI: 10.1245/s10434-014-3861-9
|View full text |Cite
|
Sign up to set email alerts
|

High STAT4 Expression is a Better Prognostic Indicator in Patients with Hepatocellular Carcinoma After Hepatectomy

Abstract: Downregulation of STAT4 in HCC indicated aggressive tumor behavior and predicted a worse clinical outcome. STAT4 might be a useful biomarker to identify patients at high risk of recurrence after hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 37 publications
4
43
1
Order By: Relevance
“…Therefore, STAT4 in hepatocytes may exert a suppressive effect on the development of HCC tumors. Other studies have shown that the role of STAT4 in the prevention of liver disease was related to inflammatory pathways . Hepatocellular carcinoma is the third most common cause of cancer death worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, STAT4 in hepatocytes may exert a suppressive effect on the development of HCC tumors. Other studies have shown that the role of STAT4 in the prevention of liver disease was related to inflammatory pathways . Hepatocellular carcinoma is the third most common cause of cancer death worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In the full-text review of the remaining 14 articles, 4 studies were further excluded since the articles did not provide extractable data. Finally, 10 previously published articles and our current cohort study were included in the meta-analysis [25,30,32,[39][40][41][42][43][44][45]. The details of the literature selection process are presented in Fig.…”
Section: Study Search and Study Characteristics In Meta-analysismentioning
confidence: 99%
“…All reports were published between 2016 and 2018. In addition to our cohort study, 9 of the previous studies were conducted in China [25,32,[39][40][41][42][43][44][45], and 1 in Japan [30]. The case numbers in each study ranged between [30,32,39,42,45], and 5 referring to liver cirrhosis [32,41,42,44,45].…”
Section: Study Search and Study Characteristics In Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in a previous study, miR‐128 played an essential role in inhibiting colorectal cancer cell proliferation by regulating NEK2 . High NEK2 expression was a tumor recurrence predictor for patients after hepatectomy treatment and an NEK2 small interfering (si)RNA injection inhibited cancer cell proliferation and peritoneal dissemination of cholangiocarcinoma in a mouse model . Furthermore, the combination of NEK2 siRNA and the chemotherapeutic agent cisplatin could enhance colorectal cancer cell apoptosis and death, suggesting an optional therapeutic approach for cancer treatment .…”
Section: Introductionmentioning
confidence: 98%